Siwa-Sisya Relationship On Ngaben Ceremony In Adat Belayu Village - I Wayan Wirta; Ida Bagus Putu Supradi (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2019)
This research entitled: "Siwa-sisya Relationship at Ngaben Ceremony in Adat Village / Pakraman Belayu, Marga, Tabanan". Obsessed with fulfilling the curiosity of the practice of holding a ceremonial ceremony involving a siwa-sisya relationship. This siwa-sisya relationship still seems to be held in Belayu. Whereas in some other traditional villages in Bali the siwa-sisya relationship has begun to diminish. This means that this research requires the disclosure of facts behind the diversity of these siwa-sisya relationship.The research with the title of the siwa-sisya relationship on the Ngaben ceremony in Belayu, which was reviewed from the perspective of phenomenal communication, had never been examined by other researchers before, so it was open for being research. Thus there are three specific objectives to be achieved by this study, namely: to describe and interpret data regarding (1) the reality of the siwa-sisya relationship on the Ngaben ceremony in Belayu; (2) social construction of siwa-sisya relationship on the Ngaben ceremony in Belayu; and (3) communication management siwa-sisya relationship on the Ngaben ceremony in Belayu. This study uses qualitative research methods, while the data collection is done through observation, interviews, and document use. The collected data is analyzed by data reduction techniques, and data display, then conclusions or verification are drawn from both. The theoretical foundation used to interpret data is social exchange theory, social construction theory, and communication management theory. This study produced three findings, namely (1) the reality model of the siwa-sisya relationship on the Ngaben ceremony in Belayu; (2) the social construction model of the siwa-sisya relationship on the Ngaben ceremony in Belayu; (3) management model of student communication on the Ngaben ceremony in Belayu. These findings are at once the conclusions of this study.